ProofWiki:Sandbox

From ProofWiki
Jump to navigation Jump to search
Welcome to the Sandbox! Play safe and have fun!

Use Proofwiki:Sandbox/Template for experimental template

Warning: The sandbox is not permanent. EXPECT ANYTHING YOU PUT HERE TO BE DELETED!



Theorem

$\forall n \in \Z_{>0}: \displaystyle \sum_{k \mathop = 0}^{n} \binom {2n} {2k} E_{2n - 2k } = 0$

where $E_k$ denotes the $k$th Euler number.


Proof

Take the definition of Euler numbers:

\(\ds \sum_{n \mathop = 0}^\infty \frac {E_n x^n} {n!}\) \(=\) \(\ds \frac {2e^x} {e^{2x} + 1}\)
\(\ds \) \(=\) \(\ds \paren {\frac {2e^x } {e^{2x} + 1 } } \paren {\frac {e^{-x } } {e^{-x } } }\) Multiply by 1
\(\ds \) \(=\) \(\ds \paren {\frac 2 {e^{x} + e^{-x} } }\)

From the definition of the exponential function:

\(\ds e^x\) \(=\) \(\ds \sum_{n \mathop = 0}^\infty \frac {x^n} {n!}\)
\(\ds \) \(=\) \(\ds 1 + x + \frac {x^2} {2!} + \frac {x^3} {3!} + \frac {x^4} {4!} + \cdots\)
\(\ds e^{-x}\) \(=\) \(\ds \sum_{n \mathop = 0}^\infty \frac {\paren {-x }^n } {n!}\)
\(\ds \) \(=\) \(\ds 1 - x + \frac {x^2} {2!} - \frac {x^3} {3!} + \frac {x^4} {4!} - \cdots\)
\(\ds \paren {\frac {e^x + e^{-x } } 2 }\) \(=\) \(\ds \paren {\sum_{n \mathop = 0}^\infty \frac {x^{2n } } {\paren {2n }!} }\)
\(\ds \) \(=\) \(\ds 1 + \frac {x^2} {2!} + \frac {x^4} {4!} + \cdots\) odd terms cancel in the sum.

Thus:

\(\ds 1\) \(=\) \(\ds \paren {\frac 2 {e^x + e^{-x } } } \paren {\frac {e^x + e^{-x } } 2 }\)
\(\ds \) \(=\) \(\ds \paren {\sum_{n \mathop = 0}^\infty \frac {E_n x^n} {n!} } \paren {\sum_{n \mathop = 0}^\infty \frac {x^{2n } } {\paren {2n }!} }\)


By Product of Absolutely Convergent Series, we will let:

\(\ds a_n\) \(=\) \(\ds \frac {E_n x^n} {n!}\)
\(\ds b_n\) \(=\) \(\ds \frac {x^{2n} } {\paren {2n }!}\)

Then:

\(\ds \sum_{n \mathop = 0}^\infty c_n\) \(=\) \(\ds \paren { \displaystyle \sum_{n \mathop = 0}^\infty a_n } \paren {\displaystyle \sum_{n \mathop = 0}^\infty b_n }\) \(\ds =1\)
\(\ds c_n\) \(=\) \(\ds \sum_{k \mathop = 0}^n a_k b_{n - k}\)
\(\ds c_0\) \(=\) \(\ds \frac {E_0 x^0} {0!} \frac {x^{0} } {0!}\) \(\ds = 1\) $c_0 = \paren {a_0 } \paren {b_{0 - 0 } } = \paren {a_0 } \paren {b_0 }$
\(\ds \leadsto \ \ \) \(\ds \sum_{n \mathop = 1}^\infty c_n\) \(=\) \(\ds \paren { \displaystyle \sum_{n \mathop = 0}^\infty a_n } \paren {\displaystyle \sum_{n \mathop = 0}^\infty b_n } - a_0 b_0\) \(\ds =0\) Subtract 1 from both sides of the equation.


$\forall n \in \Z_{\gt 0}$, term by term $c_n$ is equal to:

\(\ds c_1\) \(=\) \(\ds \frac {E_0 x^0} {0!} \frac {x^2 } {2!} + \frac {E_1 x^1} {1!} \frac {x^0 } {0!}\) \(\ds = \frac {x^2 } {2! } E_0\) $= a_0 b_1 + a_1 b_0$
\(\ds c_2\) \(=\) \(\ds \frac {E_0 x^0} {0!} \frac {x^4 } {4!} + \frac {E_1 x^1} {1!} \frac {x^2 } {2!} + \frac {E_2 x^2} {2!} \frac {x^0 } {0!}\) \(\ds = \frac {x^4 } {4! } E_0 + \frac {x^2 } {2! } E_2\) $= a_0 b_2 + a_1 b_1 + a_2 b_0$
\(\ds c_3\) \(=\) \(\ds \frac {E_0 x^0} {0!} \frac {x^6 } {6!} + \frac {E_1 x^1} {1!} \frac {x^4 } {4!} + \frac {E_2 x^2} {2!} \frac {x^2 } {2!} + \frac {E_3 x^3} {3!} \frac {x^0 } {0!}\) \(\ds = \frac {x^6 } {6! } E_0 + \frac {x^4 } {2! 2! } E_2\) $= a_0 b_3 + a_1 b_2 + a_2 b_1 + a_3 b_0$
\(\ds c_4\) \(=\) \(\ds \frac {E_0 x^0} {0!} \frac {x^8 } {8!} + \frac {E_1 x^1} {1!} \frac {x^6 } {6!} + \frac {E_2 x^2} {2!} \frac {x^4 } {4!} + \frac {E_3 x^3} {3!} \frac {x^2 } {2!} + \frac {E_4 x^4} {4!} \frac {x^0 } {0!}\) \(\ds = \frac {x^8 } {0! 8! } E_0 + \frac {x^6 } {2! 4! } E_2 + \frac {5 x^4 } {4! 0! } E_4\) $= a_0 b_4 + a_1 b_3 + a_2 b_2 + a_3 b_1 + a_4 b_0$
\(\ds \cdots\) \(=\) \(\ds \cdots\)
\(\ds c_n\) \(=\) \(\ds \frac {E_0 x^0} {0!} \frac {x^{2n} } {\paren {2n }!} + \frac {E_1 x^1} {1!} \frac {x^{2n - 2} } {\paren {2n - 2 }!} + \frac {E_2 x^2} {2!} \frac {x^{2n - 4} } {\paren {2n - 4 }!} + \cdots + \frac {E_n x^n} {n!} \frac {x^0 } {0!}\)


Grouping like even terms produces:

\(\ds \paren {\frac 1 {0! 2!} } E_0 + \paren {\frac 1 {2! 0!} } E_2\) \(=\) \(\ds 0\) $x^2$ term
\(\ds \paren {\frac 1 {0! 4!} } E_0 + \paren {\frac 1 {2! 2!} } E_2 + \paren {\frac 1 {4! 0!} } E_4\) \(=\) \(\ds 0\) $x^4$ term


Multiplying $c_n$ through by $n!$ gives:

\(\ds n! c_n\) \(=\) \(\ds \frac {E_0 x^0} {0!} \frac {n! x^n } {n!} + \frac {E_1 x^1} {1!} \frac {n! x^{n-1} } {\paren {n - 1 }!} + \cdots + \frac {E_n x^n} {n!} \frac {n! x^{0} } {0!}\) \(\ds = 0\)
\(\ds \) \(=\) \(\ds x^n \paren {\frac {n! } {0! n!} E_0 + \frac {n! } {1! \paren {n - 1 }!} E_1 + \cdots + \frac {n! } {n! 0!} E_n }\) \(\ds = 0\) factoring out $x^n$


But those coefficients are the binomial coefficients:

\(\ds n! c_n\) \(=\) \(\ds \dbinom n 0 E_0 + \dbinom n 1 E_1 + \dbinom n 2 E_2 + \cdots + \dbinom n n E_n\) \(\ds = 0\)

Hence the result.

$\blacksquare$

\(\ds \sum_{k \mathop = 0}^{n} \dbinom {2 n} {2 k} E_{2 n - 2 k}\) \(=\) \(\ds \binom {2 n} 0 E_{2 n} + \binom {2 n} 2 E_{2 n - 2} + \binom {2 n} 4 E_{2 n - 4} + \binom {2 n} 6 E_{2 n - 6} + \cdots + 1\) \(\ds = 0\)

Examples

$\begin{array}{r|cccccccccc} B_k & \dbinom n 0 & & \dbinom n 1 & & \dbinom n 2 & & \dbinom n 3 & & \dbinom n 4 & & \dbinom n 5 \\ \hline B_0 = 1 & 1 B_0 & & & & & & & & & & & = 1 \\ B_1 = -\frac 1 2 & 1 B_0 & + & 2 B_1 & & & & & & & & & = 0 \\ B_2 = +\frac 1 6 & 1 B_0 & + & 3 B_1 & + & 3 B_2 & & & & & & & = 0 \\ B_3 = 0 & 1 B_0 & + & 4 B_1 & + & 6 B_2 & + & 4 B_3 & & & & & = 0 \\ B_4 = -\frac 1 {30} & 1 B_0 & + & 5 B_1 & + & 10 B_2 & + & 10 B_3 & + & 5 B_4 & & & = 0 \\ B_5 = 0 & 1 B_0 & + & 6 B_1 & + & 15 B_2 & + & 20 B_3 & + & 15 B_4 & + & 6 B_5 & = 0 \\ \end{array}$


Also see